The Influence of Digital Leadership and Organizational Commitment on Employee Performance with Job Satisfaction as an Intervening Variable - Wahyu Saputra Akbar; Aldri Frinaldi (GoAcademica Research & Publishing, 2026)
This study aims to analyze the partial effects of digital leadership and organizational commitment on employee performance, with job satisfaction acting as an intervening variable at the Regional Secretariat of Sijunjung Regency. The research employs a quantitative approach with an explanatory research design. The population consists of 76 respondents, and a saturated sampling technique was applied. Data were collected through a questionnaire using a Likert scale to measure the indicators of each statement item. The analytical technique used is Partial Least Square–Structural Equation Modeling (PLS-SEM). The results show that digital leadership significantly affects employee performance and job satisfaction; job satisfaction significantly affects employee performance; organizational commitment does not significantly affect either employee performance or job satisfaction; job satisfaction is able to mediate the effect of digital leadership on employee performance; and job satisfaction is not able to mediate the effect of organizational commitment on employee performance at the Regional Secretariat of Sijunjung Regency. From the perspective of this study, strengthening digital leadership should be regarded as a strategic priority, as it has been shown to enhance both job satisfaction and employee performance, directly as well as indirectly. Job satisfaction needs to be managed systematically as a key factor that reinforces the effectiveness of digital leadership in driving organizational performance. Conversely, organizational commitment requires a new, more adaptive approach, since it was not found to have a significant effect, nor to act as a mediating mechanism, in improving employee performance within the Regional Secretariat of Sijunjung Regency.